Wealth creation- facilitating the mobility of engineering services via the Malaysian Service Providers Confederation (MSPC) - Beng, Choo Kok, Ir. (The Institution of Engineers, Malaysia (IEM), 2015)
Link to publisher’s homepage at http://www.myiem.org